Postoperative Pain Management in Rhinoplasty: A Double Blind Randomized Controlled Trial - Kandathil, Cherian Kurian; Spataro, Emily A.; Saltychev, Mikhail; Kalebjian, Roushig; Patel, Priyesh N.; Kim, Cherine H.; Akkina, Sarah R.; Kimura, Kyle S.; Rossi-Meyer, Monica; Longino, Elizabeth S.; Truong, Henry; Most, Sam P. (Mary Ann Liebert, 2026)
Background:
There is inadequate evidence for the utilization of nonnarcotic pain medications for postoperative pain management following rhinoplasty.
Objective:
To compare the effectiveness of opioid and non-opioid medications for postoperative pain control in rhinoplasty as measured by a visual analog scale (VAS) on postoperative days 0–5.
Methods:
In this double-blind randomized controlled clinical trial, adult patients who underwent primary rhinoplasty at a tertiary center were enrolled from August 2019 to October 2024. Patients were randomized to receive either a combination of acetaminophen (325 mg) and hydrocodone (5 mg) or acetaminophen (325 mg) and ibuprofen (200 mg), 1–2 tablets every 4 h for five postoperative days. Tramadol (50 mg) was prescribed for breakthrough pain.
Results:
A total of 130 patients (65 per group) completed the study. The average age (SD) was 32 (10.7) years. The majority were women (77%), White (68%), and underwent combined functional and aesthetic rhinoplasty (52%). There was no difference detected in mean postoperative pain (VAS) scores recorded on postoperative days 0–5, between treatment groups (p = 0.156). Among side effects, only itchiness was significantly higher (p = 0.001) in the hydrocodone–acetaminophen group.
Conclusion:
This trial demonstrates a lack of difference between opioid and non-opioid pain medications in postoperative pain control after rhinoplasty.